DEVELOPMENT AND EVALUATION OF JAPANESE QUAIL EGG PICKLE PRODUCT TO ENSURE FOOD AND NUTRITION SECURITY - M. Vimalarani; P.R. Nisha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of the present study was to standardize and evaluate and acceptance of Japanese quail egg pickle. A simple, cost-effective and efficient technology need to be developed for pickling of Japanese quail eggs for storage at ambient temperature and marketing it in a ready-to-eat form for at least 6 months. Results on sensory evaluation revealed that highly acceptable nutrient rich Japanese quail egg pickle prepared by soaking in citric acid solution was superior than those made from other trials and recorded highest sensory score of 8.0. Storage study showed that the pickles stored in both food grade pouches and glass bottles could be stored up to six months. Training programmes were organized to demonstrate Japanese quail egg pickle production among farmers, farm women and SHG women. Feedback of the farmers and SHG showed that the Japanese quail egg pickles was tasty and can be used as side dish for any food item, easy to prepare and market. A case study on a successful entrepreneur showed that Japanese quail egg pickle had a good demand among the people suffering from respiratory problems. The pickle was sold as 200g bottle with a profit margin of 40 per cent. Developed Japanese quail egg pickles are also sold in 200 g bottle at the KVK Rural mart with FSSAI license and labeling.